Information and Communication Technologies in Tourism 2018 2017
DOI: 10.1007/978-3-319-72923-7_19
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Online Reviews of Hotel Service Attributes: A Cross-National Study of Selected Countries in Africa

Abstract: Online travel reviews are paramount to trip planning because they help consumers' form images of destinations. Despite ample studies on hotel service attributes, knowledge is scarce regarding culturally nuanced attributes, including security perceptions. This study examines consumers' perceptions of service attributes and security/safety concerns of hotels in Africa. Data were extracted from three hotel categories (3, 4, and 5-stars), which were based on TripAdvisor rankings from Egypt, Ghana, Kenya, Nigeria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(35 reference statements)
0
12
0
2
Order By: Relevance
“…There are many studies on the important role ICT plays in an economy (Evans, 2018b; Evans, 2018c; Wang, 1999). While studies such as Bethapudi (2013) have argued that ICT plays a major role in tourism development and has become an inevitable contributor to tourism industry expansion, most analyses in the literature have largely ignored the important link between ICT and tourism, exceptions being Ankomah and Larson (2018), Firoiu and Croitoru (2013), Ma et al (2003), and Ukpabi et al (2018). Ma et al (2003) examined how ICT and the Internet have gradually changed the tourism industry in China, the impact of those changes, and where the changes are leading China’s tourism industry.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on the important role ICT plays in an economy (Evans, 2018b; Evans, 2018c; Wang, 1999). While studies such as Bethapudi (2013) have argued that ICT plays a major role in tourism development and has become an inevitable contributor to tourism industry expansion, most analyses in the literature have largely ignored the important link between ICT and tourism, exceptions being Ankomah and Larson (2018), Firoiu and Croitoru (2013), Ma et al (2003), and Ukpabi et al (2018). Ma et al (2003) examined how ICT and the Internet have gradually changed the tourism industry in China, the impact of those changes, and where the changes are leading China’s tourism industry.…”
Section: Theory and Literature Reviewmentioning
confidence: 99%
“…ICT presents huge opportunities for growing and strengthening Africa’s tourism development (Adukaite and Cantoni, 2016; Adukaite et al, 2016; Ankomah and Larson, 2018; Booyens and Rogerson, 2016; Ukpabi et al, 2018) by “enabling direct promotion and commercialization of local tourism offerings in international markets, reducing dependence on big foreign intermediaries” (Petti and Passiante, 2009: 46). Tourism destinations are able to increase online presence via the Internet and become competitive in the global tourism market through off-line connectivity that offers the requisite tools and applications to undertake effective tourism management through collaboration, clustering, and links with private and public tourism and tourism-related actors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the qualitative analysis conducted on the data extracted from Twitter, this study also used Microsoft Excel 2016 for descriptive statistics of following, followers, ratio, number of tweets, months used on Twitter and tweets per month based on two groups and chi-square test. The analysis technique adopted was inferred from the studies of Ukpabi, Olaleye, Mogaji, and Karjaluoto (2018) and Ryan, De Jong, and Wagner (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the context of Africa considering countries from distinctive regions (Nigeria, Kenya, South Africa, Ghana and Egypt), Ukpabi et al, [50] reported a cross-national study on consumers' perception and reviews on hotel service. In a highcontext culture like Africa, interpersonal relationship are important to social cohesion regarding staff relational services.…”
Section: Politeness In Multiple Culturesmentioning
confidence: 99%